'Then David Began to Sing this Song' Composition and Hermeneutics in Pseudo-Philo's Psalm of David (LAB 59.4) - Botner, Max 1985- (2018)
Despite burgeoning interest in Pseudo-Philo's use of the Jewish scriptures, little to-date has been said about the writer's psalm of David (LAB 59.4). In fact, outside of Strugnell's reconstruction of the psalm's Vorlage (1965) and Jacobson's two-volume commentary (1996), virtually nothing has been written about this section of Liber Antiquitatum Biblicarum. This article demonstrates that LAB 59.4 constitutes a sophisticated piece of scriptural exegesis that fits within the writer's well-established hermeneutical strategies. It identifies plausible intertexts comprising LAB's psalm and traces the hermeneutical techniques that attracted Pseudo-Philo to these passages of scripture.
Keywords: LAB 59.4; David; Dead Sea Scrolls; Liber antiquitatum biblicarum (LAB); Psalm 91; Psalms (Psalter); Pseudepigrapha; Pseudo-Philo